2012
DOI: 10.1007/978-3-642-27645-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Transfer in Reinforcement Learning: A Framework and a Survey

Abstract: Transfer in reinforcement learning is a novel research area that focuses on the development of methods to transfer knowledge from a set of source tasks to a target task. Whenever the tasks are similar, the transferred knowledge can be used by a learning algorithm to solve the target task and significantly improve its performance (e.g., by reducing the number of samples needed to achieve a nearly optimal performance). In this chapter we provide a formalization of the general transfer problem, we identify the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
146
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(156 citation statements)
references
References 38 publications
0
146
0
3
Order By: Relevance
“…In this scenario, usually referred 25 to as multi-task reinforcement learning (MTRL), the 26 objective is to simultaneously solve multiple tasks and 27 exploit their similarity to improve the performance w.r.t. 28 single-task learning (we refer to [28] and [16] for a com- …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, usually referred 25 to as multi-task reinforcement learning (MTRL), the 26 objective is to simultaneously solve multiple tasks and 27 exploit their similarity to improve the performance w.r.t. 28 single-task learning (we refer to [28] and [16] for a com- …”
mentioning
confidence: 99%
“…Results of the first experiment in the chain walk domain comparing GL-FQI and LASSO-FQI. On the y axis we have the average regret computed according to Equation (16). On the x axis we have the total number of dimensions d, including noise dimensions, on a logarithmic scale.…”
mentioning
confidence: 99%
“…RL has a strong relationship with supervised learning and unsupervised learning, so it is quite appealing to introduce more machine learning methods to RL problems. For example, there have been some research on combining transfer learning with RL [114] , aiming to solve different tasks with transferred knowledge. When the training data set is large, the computational cost of batch RL algorithms will become a serious problem.…”
Section: Discussionmentioning
confidence: 99%
“…5). In addition, it has been shown that some learning mechanisms, such as reinforcement learning and transfer learning, can be helpful for constructing more complex intelligent reasoning systems (Lazaric, 2012). Furthermore, lifelong learning (Lazer et al, 2014) is the key capability of advanced intelligence systems.…”
Section: Cross-media Knowledge Evolution and Reasoningmentioning
confidence: 99%